Three new species of Stibeutes and Gnotus (Hymenoptera: Ichneumonidae) from holm-oak and cork-oak Mediterranean forests (Insect Systematics & Evolution, 2004)
The new species Stibeutes hirsutus, S. calderonae and Gnotus klausi from Spanish holm-oak and cork-oak woods are described and illustrated. Data on their habitat and the phenology of S. hirsutus are reported. The species S. breviareolatus collected in a cork-oak forest is recorded for the first time for Spain. New keys for the Gnotus tenuipes species group and for the Spanish species of Stibeutes are provided.

Three new species of Stibeutes and Gnotus (Hymenoptera: Ichneumonidae) from holm-oak and cork-oak Mediterranean forests - Bordera, Santiago; Hernández-Rodríguez, Estefanía (Insect Systematics & Evolution, 2004)
The new species Stibeutes hirsutus, S. calderonae and Gnotus klausi from Spanish holm-oak and cork-oak woods are described and illustrated. Data on their habitat and the phenology of S. hirsutus are reported. The species S. breviareolatus collected in a cork-oak forest is recorded for the first time for Spain. New keys for the Gnotus tenuipes species group and for the Spanish species of Stibeutes are provided.
Keywords: Gnotus; habitat; morphology; new species; phenology (PG); Stibeutes